Let's get the same terms on the same side. I am going to remove 5x from both sides of the equation by subtracting 5x
5x - 5x -7 = 7x -5x - 17 -7 = 2x - 17 now lets remove the 17 from both sides -7 + 17 = 2x (why do we add 17? Think of 2x -17 as 2x + -17. Tor remove a negative number we add it. Now we finally have 10=2x and if we divide both sides by 2
<u>10</u> = <u>2x</u><u> </u>2 2 we get that x = 5 <u />Let's check by substituting 5 in the original equation: 5(5) - 7 = 7(5) - 17 25 - 7 = 35 - 17 18 = 18